Obstacles to scientific research from the point of view of faculty members in the Department of Electromechanical Engineering at the University of Technology (Journal of the College of Basic Education, 2022)
The study aimed to identify the obstacles of scientific research facing faculty members in the Department of Electromechanical Engineering at the University of Technology. The sample of the study is (126) faculty members in the Department of Electromechanical Engineering at the University of Technology, who were selected using the random stratified method.